Association Between Electrocardiographic Abnormalities and In-Hospital Adverse Outcome in COVID-19 Patients - Begum, Anjuman; Chowdhury, Wadud; KS, Suman; KC, Arnab; Akteruzzaman, Md.; Sushanta, Barua (Journal of Cardiology and Cardiovascular Medicine, 2024)
Background: SARS-CoV-2 is increasingly recognized for its cardiovascular complications. To address the knowledge gap in our region, this study investigated the relationship between electrocardiographic (ECG) features and in-hospital mortality among COVID-19 patients. Methods: A prospective cohort study was conducted involving 140 RT-PCR-confirmed COVID-19 patients at Dhaka Medical College Hospital from August 2021 to July 2022. Patients were divided into two groups based on ECG findings: normal (Group A) and abnormal (Group B). Clinical data and ECG parameters were analyzed using SPSS 24.0. Results: Patients with abnormal ECGs were older, more likely male, and presented with higher rates of dyspnea and palpitations. They were also at increased risk of severe COVID-19 and had longer hospital stays. In-hospital mortality was significantly higher in Group B (21.4% vs.4.3%). ST-T changes and atrial fibrillation were associated with increased mortality. Independent predictors of in-hospital mortality included ECG abnormalities and admission SpO₂ < 90%. Conclusion: ECG abnormalities are significantly associated with adverse outcomes in COVID-19 patients. Further large-scale studies are warranted to strengthen these findings.